Kontribusi Daya Ledak Otot Tungkai Terhadap Kecepatan Lari Pada Tim Sepakbola MAN 2 Model Pekanbaru - Effendi, Amri Effendi; Juita, Ardiah Juita; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The results of this study can be concluded that the explosive power of leg muscle influence on speed of running, and the purpose of this study is to find out how much the relationship  between the explosive power of leg muscle influence on speed of running. The type of this study is a correlation study design to find out the significance relationship between leg muscle explosive power of with a population of football teams MAN 2 Model Pekanbaru which consists of 25 people. Sampling on this study is use  the total sampling.The  sample in this study there is the whole of the population, so sample totaling 25 people. While the instrument is carried out in this study is a vertical jump test using jump MD and test of speed of run a 100-yard. Then the data analyzed with statistic, to test for normality with lieliefour  test, the proposed hypothesis is the relationship leg muscle explosive power of with speed of running. From the analysis of the data using lieliefours tests on variables X and Y, which is obtained L = 0,1009 whereas L = 0,173, so if L = 0,1009 <L = 0,173 then the data is normally distributed, with a correlation coefficient of r = 0,65 > r = 0,396,and coefficient determination is 42 % . Thus, the data is otherwise normal. Conclusion hypothesis is accepted, thus there is a correlation between the explosive power of leg muscle influence on speed of running in MAN 2 Model Pekanbaru. Keyword : The explosive power of leg muscle , Speed of running